MUNICIPAL ENERGY MANAGEMENT AS A PUBLIC POLICY TO PROMOTE LOCAL-BASED ENERGY TRANSITION - Walmeran José Trindade Júnior; Cidoval Moraes de Sousa (Revista Tempo do Mundo, 2023)
The purpose of this work is to discuss the feasibility of municipal energy management in the context of the energy transition. It is based on the assumption that municipal energy management, having as its pillars the use of renewable energy sources, energy conservation and the involvement of society in the elaboration, implementation and control of this sustainable energy policy, not only significantly reduces energy expenditure, how it contributes to the construction of a fair, inclusive, participatory and locally based energy transition.